KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SMAN 1 PARINGIN - Miranti Miranti (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
One of the educational problems facing our nation is the quality of education. Various efforts have been made to improve the quality of national education, including through various trainings and improving teacher competence, procuring books and learning tools, improving educational facilities and infrastructure, and improving the quality of school management. Leadership is one of the factors that determine the success of SBM implementation. School-Based Management gives flexibility to schools to manage their potential by involving all stakeholders to improve the quality of the school. Because the school has such broad authority, the presence of a leader figure is very important. Understanding of the nature of leadership. In implementing SBM, school principals need to have strong, participatory and democratic capabilities. This research uses a qualitative approach in a descriptive form. The use of descriptive methods in this study with the aim of describing an implementation of school principal leadership in implementing school-based management by first analyzing the implementation process. The implementation of School Based Management (SBM) at SMAN 1 Paringin is participatory. This management gives authority from the school, and then the school delegates it to each teacher and its employees. All teachers and employees feel involved from planning, implementing, and evaluating school programs. The principle of decentralization views that problems that arise in schools will be adjusted as best as possible if the solution is left to the party closest to the existence of the problem. In solving educational problems in schools, those who know the most about the problem are the school members themselves, especially teachers, staff, principals and parents of students. The application of participatory management improves the quality and service of education so that SMAN 1 Paringin can compete and produce quality graduates both academically and non-academically. SBM will work well if school members have initiative in carrying out their work and each individual's initiative is valued. As for what happened at SMAN 1 Paringin, there was still a lack of initiative by school members due to a lack of sense of belonging to the school.